Pengaruh Pemberian Biochar Dan Pupuk Urea Terhadap Pertumbuhan Dan Hasil Tanaman Pakcoy (Brassica rapa. L) - I Made Baskara Adi; Made Suarta; Anak Agung Sagung Putri Risa Andriani (GEMA AGRO, 2022)
This research was conducted in the greenhouse of the Faculty of Agriculture, Warmadewa University, Denpasar, starting from October 25 to November 29, 2019. This study aims to determine the effect of giving biochar and urea fertilizer on the growth and yield of pakcoy (Brassica rapa L). The research was conducted through this experimental method using a randomized block design (RAK) with two treatment factors. The first factor is biochar which consists of four dosage levels, namely: B0 (0 tons ), B1(5 tons ), B2 (10 tons ) dan B3 (15 tons ), the second factor is urea fertilizer which consists of three levels, namely: U1 (50 kg U2 (100 kg ) dan U3 (150 kg )The results showed that the treatment of biochar and urea fertilizer and their interactions had no significant effect on the growth and yield of pakcoy plants.